Robotic versus thoracoscopic lung resection: A systematic review and meta-analysis - Emmert, Alexander; Straube, Carmen; Buentzel, Judith; Roever, Christian (Medicine (Baltimore), 2017)
Robotic video-assisted surgery (RVATS) has been reported to be equally effective to video-assisted surgery (VATS) in lung resection (pneumonectomy, lobectomy, and segmentectomy). Operation time, mortality, drainage duration, and length of hospitalization of patients undergoing either RVATS or VATS are compared in this meta-analysis. A systematic research for articles meeting our inclusion criteria was performed using the PubMed database. Articles published from January 2011 to January 2016 were included. We used results of reported mortality, operation time, drainage duration, and hospitalization length for performing this meta-analysis. Mean difference and logarithmic odds ratio were used as summary statistics. Ten studies eligible were included into this analysis (5 studies for operation time, 3 studies for chest in tube days, 4 studies for length of hospitalization, and 6 studies for mortality). We were able to include 3375 subjects for RVATS and 58,683 subjects for VATS. Patients were mainly treated for lung cancer, metastatic foci, and benign lesions. We could not detect any difference between operation time; however, we found 2 trends showing that drainage duration and length of hospitalization are shorter for following RVATS than for following VATS. Mortality also is lower in patients undergoing RVATS. Therefore, we conclude that RVATS is a suitable minimal-invasive procedure for lung resection and suitable alternative to VATS. RVATS is as time-efficient as VATS and shows a trend to reduced hospital stay and drainage duration. More and better studies are required to provide reliable, unbiased evidence regarding the relative benefits of both methods.